Vpliv vakuumskega razplinjevanja polimerov na kontaktno upornost Ag kontaktov v hermetičnih relejih - Koller, Lidija (Kovine zlitine tehnologije, 1999)
The purpose of our study is to increase the reliability of electric contacts of AgNi015 alloy which would apparently substitute more expensive contact materials on the basis of gold. Contact reliability strongly depends on the time stability of the contact resistance. Vapour released from the polymer relay parts condenses on the contacts as compact films that incrase the contact resistance. Relay parts made of four different materials (Crastin, Lexan, Ultramide, Araldite) were otugassed in high vacuum (?$1x10^{-6} mbar$?) at 135°C for 48 hours. Then the parts were incorporated into the relays and the contact resistance was measured in definite time intervals. The same was done also with the polymer parts that were not outgassed. We found out that the contact resistance directly depends on the outgassing rate of the material which determines the state of the contact surface.
Keywords: vakuumsko razplinjevanje; kontaktni materiali; polimeri; releji; kontaktna upornost